Design and Implementation of Web-Based Point of Sale and Photo Studio Management System Using MVC Architecture - Haniel Pratama; Andreas Akar; Alfa Rivales Matal; Abram Pangidoan Tambak; Cahya Evendy (International Journal of Computer and Information System (IJCIS), 2026)
Photo studios frequently experience operational challenges in integrating cashier transactions, schedule management for photo sessions, and real-time inventory tracking. Manual recording systems often lead to fatal data losses and schedule conflicts. This research aims to design and implement a web-based Point of Sale and studio management information system named Dthree POS to resolve these operational bottlenecks. The system development utilizes the Prototyping method, allowing iterative design improvements from initial sketches to high-fidelity user interfaces. The application is built upon the Model View Controller architecture using the Laravel framework, which effectively separates business logic from data presentation. The results show that the system successfully integrates the management of physical products with limited stock and service products with unlimited availability. Furthermore, the implementation of pessimistic database locking and atomic transactions effectively prevents race conditions during simultaneous checkout processes. The system also accommodates a dynamic pricing hierarchy for different customer types and automatically converts completed studio bookings into final sales data. In conclusion, Dthree POS provides an empirical and highly reliable solution to digitalize and streamline the entire photo studio business workflow.